The Effectiveness Of Specialized Breathing Exercises On Improving 60-Meter Sprint Speed For Fifth-Grade Students At SDN 37 Krui Ngaras District - Sukmana, Fajar; Susilawati, Dewi (Journal of Sport Education, Coaching, and Health (JOCCA), 2024)
The 60-meter sprint is one of the events in athletics that requires optimal speed and endurance. This study aims to test the effectiveness of specialized breathing exercises in improving the 60-meter sprint speed among fifth-grade elementary school students. The research employs an experimental design with a control group. The sample consists of fifth-grade students who are randomly divided into two groups: the experimental group, which receives specialized breathing exercises, and the control group, which does not receive any treatment. Data is collected through 60-meter sprint tests conducted before and after the intervention. Data analysis uses a t-test to compare the average sprint times between the two groups. The results of this study are expected to contribute to the development of short-distance running training programs, particularly for school-age children.